Science Learning in Primary Schools: A Comprehensive Analysis of Curriculum Merdeka Implementation - Jamilah; Astuti, Yeni Puji (Journal of Education Reseach and Evaluation, 2025)
Implementation in science learning faces challenges related to school readiness, teacher competence, and the effectiveness of competency-based evaluation methods. This study aims to evaluate science learning based on the Merdeka Curriculum in primary schools using the CIPP (Context, Input, Process, Product) evaluation approach. This research employs a mixed-method research approach, which is applied when researchers have questions that need to be examined in terms of outcomes and processes, combining both quantitative and qualitative methods in a single study. The research population is located in Sumenep Regency, with 207 primary school students comprising 105 female students and 102 male students. Data collection techniques in this study include both tests and non-test methods. Test instruments consist of skill tests, written tests, and oral tests, while non-test instruments include questionnaires. The results of the study indicate that policy support and school resources play a significant role in creating a conducive learning environment (Context). Teacher competency, particularly in designing competency-based evaluations, is a key factor in the successful implementation of the curriculum (Input). Project-based and participatory learning processes have been proven to increase student engagement (Process). In the Product dimension, learning outcomes show improvement among students in schools with strong implementation support. However, limited resources in some schools remain a challenge to optimizing science learning.